O SUCESSO E O FRACASSO DO ALFABETIZANDO REFLETIDO NO SEU DISCURSO - Pernambuco, Déa Lucia Campos (Intercâmbio, 2010)
This study aims at investigating and analysing two groups of students about their success or failure at the end of the first grade. Social Imaginary, Representation Theory, Subject Analysis, French tendencies of Discourse Analysis, and language conceptions while result of social structures were used. The realized analyses are supposed to allow that these representations are showed as re-apresentations that the students have by themselves; they are derived from school, family and society discourses.